2017
DOI: 10.1002/jsfa.8310
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of pectic hydrocolloids and phenolics from huanglongbing related dropped citrus fruit

Abstract: The continuous steam explosion of pre-harvest dropped citrus fruit provides an enhanced, environmentally friendly method for the release and recovery of valuable coproducts from wasted biomass. Published 2017. This article is a U.S. Government work and is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…However, within each hybrid group, the polydispersity of the acid extracted pectin was significantly lower than the STEX material (p < 0.0001 for each hybrid group). Polydispersity values reported here for the STEX biomass are much lower than those reported for juice extracted sweet orange peel or pre-harvest dropped Hamlin sweet oranges [24,25] but in agreement with those reported for HLB infected sweet oranges [23].…”
Section: Recovery and Macromolecular Properties Of Pectic Hydrocolloids From Stexsupporting
confidence: 91%
See 1 more Smart Citation
“…However, within each hybrid group, the polydispersity of the acid extracted pectin was significantly lower than the STEX material (p < 0.0001 for each hybrid group). Polydispersity values reported here for the STEX biomass are much lower than those reported for juice extracted sweet orange peel or pre-harvest dropped Hamlin sweet oranges [24,25] but in agreement with those reported for HLB infected sweet oranges [23].…”
Section: Recovery and Macromolecular Properties Of Pectic Hydrocolloids From Stexsupporting
confidence: 91%
“…Therefore, STEX was explored as a pretreatment method to extract and isolate high-value compounds within citrus residues. It was demonstrated that pectic hydrocolloids, sugars, phenolics, flavonoids, and volatiles from sweet orange and grapefruit residues could be obtained in high yields using STEX [ 18 , 20 , 21 , 22 , 23 , 24 , 25 ]. The total potential value that could be obtained from these citrus residues using STEX in a single season ranged between USD 70 and 760 million depending on the variety processed in Florida [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The slurries were centrifuged at a relative centrifugal force of 15,000 × g for 20 min at 4 • C. The supernatant was recovered, and the pellet was washed two more times as described above, with 100-g deionized water, for a total of three washes per replicate. An aliquot of each wash supernatant was used for determination of its carbohydrate composition via enzymatic hydrolysis, in duplicate (12). The remaining portions from each wash were pooled and preserved with lithium azide (0.02%, wt/wt).…”
Section: Recovery Of Pectic Hydrocolloidsmentioning
confidence: 99%
“…To accomplish this, steam explosion was explored as a means of extracting maximum amounts of these high-value compounds. Pectic hydrocolloids, sugars, volatiles, phenolics, and flavonoids have been extracted from orange juice-processing residues previously, using a continuous pilot scale steam explosion system ( 10 12 ). This previous study has focused only on the sweet orange varieties used for orange juice processing in Florida.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, numerous alternative technologies have been proposed for pectin extraction, but none have been commercialized (Adetunji et al., 2017; Fishman et al., 2006; Kaya et al., 2014). We have developed a continuous process to release pectic hydrocolloids from their intracellular entrapment using steam explosion (Cameron et al., 2016, 2017a, 2017b; Dorado et al., 2017), which has the benefit of enabling pectin extraction from steam‐exploded citrus fruit peel using a simple water wash. Data from these previous studies suggest that the observed low M w and [ ƞ ] may have resulted from the processing variables of temperature and time‐at‐temperature. To test this hypothesis, we utilized a static, batch steam explosion system (Grohmann et al., 2013) to process a stabilized lime pectin peel at temperatures ranging from 120 to 150°C and for hold times of 1, 2, and 3 min.…”
Section: Introductionmentioning
confidence: 99%